2017
DOI: 10.1186/s40246-017-0121-7
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the angiogenic and lymphangiogenic pathways are associated with lymphedema caused by Wuchereria bancrofti

Abstract: BackgroundLymphedema (LE) is a chronic clinical manifestation of filarial nematode infections characterized by lymphatic dysfunction and subsequent accumulation of protein-rich fluid in the interstitial space—lymphatic filariasis. A number of studies have identified single nucleotide polymorphisms (SNPs) associated with primary and secondary LE. To assess SNPs associated with LE caused by lymphatic filariasis, a cross-sectional study of unrelated Ghanaian volunteers was designed to genotype SNPs in 285 LE pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
2
15
0
3
Order By: Relevance
“…In this study lymphedema cases recorded were significantly higher in females than in males, which is consistent with many reported cases in literature [ 27 30 ]. However, the cases identified among the various age groups as well as the districts were not different.…”
Section: Discussionsupporting
confidence: 93%
“…In this study lymphedema cases recorded were significantly higher in females than in males, which is consistent with many reported cases in literature [ 27 30 ]. However, the cases identified among the various age groups as well as the districts were not different.…”
Section: Discussionsupporting
confidence: 93%
“…demonstrated that in W. bancrofti infected individuals with filaria-induced pathology, MMPs and their counterparts, the tissue inhibitor of metalloproteinases (TIMPs), are elevated 76 . Previous studies from our institute demonstrated that single nucleotide polymorphisms (SNPs) in MMP2 are a risk factor to develop lymph edema 77 , suggesting that MMP9 could also be involved in the development of filarial pathology. Similarly, SNPs of the pattern recognition receptors TLR4, NOD1 and NOD2 were shown to be associated with patent lymphatic filariasis 78 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, gene variants of FOXC2 and FLT4 (encodes VEGFR3) have been identified in lymphatic filariasis, the most common form of secondary lymphedema worldwide, and caused by infection with filarial worms, primarily Wuchereria bancrofti (56, 974). In addition, SNPs in the genes that encode VEGFR3, MMP-2, and carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM-1), all of which have roles in lymphangiogenesis, have also been identified to have significance in lymphatic filariasis (254). It is plausible that these gene variants may have a moderate impact lymphatic wall integrity or lymphatic valve maintenance, lowering the “margin of safety” against edema with high fluid loads, while not impairing lymph flow under normal fluid loads.…”
Section: Lymphedemamentioning
confidence: 99%